The complete genome sequence, occurrence and host range of Tomato mottle mosaic virus Chinese isolate. Issue 1 (December 2017) - Li, Yueyue; Wang, Yang; Hu, John; Xiao, Long; Tan, Guanlin; Lan, Pingxiu; Liu, Yong; Li, Fan
Abstract Background Tomato mottle mosaic virus (ToMMV) is a recently identified species in the genusTobamovirus and was first reported from a greenhouse tomato sample collected in Mexico in 2013. In August 2013, ToMMV was detected on peppers (Capsicum spp.) in China. However, little is known about the molecular and biological characteristics of ToMMV. Methods Reverse transcription-polymerase chain reaction (RT-PCR) and rapid identification of cDNA ends (RACE) were carried out to obtain the complete genomic sequences of ToMMV. Sap transmission was used to test the host range and pathogenicity of ToMMV. Results The full-length genomes of two ToMMV isolates infecting peppers in Yunnan Province and Tibet Autonomous Region of China were determined and analyzed. The complete genomic sequences of both ToMMV isolates consisted of 6399 nucleotides and contained four open reading frames (ORFs) encoding 126, 183, 30 and 18 kDa proteins from the 5' to 3' end, respectively. Overall similarities of the ToMMV genome sequence to those of the other tobamoviruses available in GenBank ranged from 49.6% to 84.3%. Phylogenetic analyses of the sequences of full-genome nucleotide and the amino acids of its four proteins confirmed that ToMMV was most closely related toTomato mosaic virus (ToMV). According to the genetic structure, host of origin and phylogenetic relationships, the available 32 tobamoviruses could be divided into at least eight subgroups based on the host plant family they infect: Solanaceae-, Brassicaceae-, Cactaceae-, Apocynaceae-, Cucurbitaceae-, Malvaceae-, Leguminosae-, and Passifloraceae-infecting subgroups. The detection of ToMMV on some solanaceous, cucurbitaceous, brassicaceous and leguminous plants in Yunnan Province and other few parts of China revealed ToMMV only occurred on peppers so far. However, the host range test results showed ToMMV could infect most of the tested solanaceous and cruciferous plants, and had a high affinity for the solanaceous plants. Conclusions The complete nucleotide sequences of two Chinese ToMMV isolates from naturally infected peppers were verified. The tobamoviruses were divided into at least eight subgroups, with ToMMV belonging to the subgroup that infected plants in the Solanaceae. In China, ToMMV only occurred on peppers in the fields till now. ToMMV could infect the plants in family Solanaceae and Cucurbitaceae by sap transmission.